2018
DOI: 10.1038/s41570-018-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Studying glycobiology at the single-molecule level

Abstract: Attempts to elucidate the roles of carbohydrate-associated structures in biology have led to the distinct field of glycobiology research. The focus of this field has been in understanding the evolution, biosynthesis and interactions of glycans, both individually and as components of larger bio-molecules. However, as most approaches for studying glycans (including mass spectrometry and various binding assays) use ensemble measurements, they lack the precision required to uncover the roles of glycoconjugates, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 102 publications
(116 reference statements)
0
34
0
Order By: Relevance
“…Carbohydrate chemistry, due to the structural diversity of sugars with unique shape and binding modes, can be applied to develop a broad range of complex therapeutic molecules and drugs . Glycoconjugates is the general classification for carbohydrates covalently linked to other chemical species, termed aglycones . They play a fundamental role in normal cell functions as well as in major disease pathologies including cancer, cardiovascular and inflammatory diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate chemistry, due to the structural diversity of sugars with unique shape and binding modes, can be applied to develop a broad range of complex therapeutic molecules and drugs . Glycoconjugates is the general classification for carbohydrates covalently linked to other chemical species, termed aglycones . They play a fundamental role in normal cell functions as well as in major disease pathologies including cancer, cardiovascular and inflammatory diseases .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Glycoconjugates is the general classification for carbohydrates covalently linked to other chemical species, termed aglycones. [2] They play a fundamental role in normal cell functions as well as in major disease pathologies including cancer, cardiovascular and inflammatory diseases. [3][4][5][6] Very often the aglycon part is of special interest with application in drug discovery; it can bind to a specific target, while the sugar moiety can enhance the transport properties through transporters and increase water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the ability of intermolecular interactions to communicate structural specificity of carbohydrates to protonated aromatic molecules in non-covalent complexes,i solated and cooled in the gas phase.Our study revealed that small structural differences between carbohydrate isomers of any type,i ncluding enantiomers,a re accurately communicated by these interactions to aromatic molecules as detectable changes in their electronic excitation spectra. [5] Them onomeric structural units of carbohydrates exist in av ariety of stereoisomeric forms,s uch as d/l-enantiomers, epimers,a nd a/b-anomers.F or instance,acyclic aldohexo-pyranose has 5stereogenic centers,which implies an existence of 2 5 = 32 stereoisomers (for example, a-d-glucose, b-lgalactose,e tc. [1] Existing in myriads of structural forms,m any of which are isomeric,c arbohydrates may function as messenger and recognition molecules in signaling the type and the state of living cells in complex chains of biological processes.…”
mentioning
confidence: 99%
“…[1] Existing in myriads of structural forms,m any of which are isomeric,c arbohydrates may function as messenger and recognition molecules in signaling the type and the state of living cells in complex chains of biological processes. [5] Them onomeric structural units of carbohydrates exist in av ariety of stereoisomeric forms,s uch as d/l-enantiomers, epimers,a nd a/b-anomers.F or instance,acyclic aldohexo-pyranose has 5stereogenic centers,which implies an existence of 2 5 = 32 stereoisomers (for example, a-d-glucose, b-lgalactose,e tc. [5] Them onomeric structural units of carbohydrates exist in av ariety of stereoisomeric forms,s uch as d/l-enantiomers, epimers,a nd a/b-anomers.F or instance,acyclic aldohexo-pyranose has 5stereogenic centers,which implies an existence of 2 5 = 32 stereoisomers (for example, a-d-glucose, b-lgalactose,e tc.…”
mentioning
confidence: 99%
See 1 more Smart Citation